1993
DOI: 10.1126/science.7903123
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of HIV-Specific Cell-Mediated Immune Responses by Interleukin-12 in Vitro

Abstract: Peripheral blood mononuclear cells (PBMCs) from many asymptomatic individuals infected with human immunodeficiency virus-type 1 (HIV) are unresponsive as measured by in vitro T cell proliferation and interleukin-2 (IL-2) production to influenza virus and synthetic peptides of HIV envelope (Env). Strong influenza virus- and Env-stimulated IL-2 responses and T cell proliferation were restored when cultures were stimulated in the presence of IL-12. Interferon-gamma production by PBMCs from HIV seropositive (HIV+)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
173
2

Year Published

1996
1996
1998
1998

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 380 publications
(187 citation statements)
references
References 30 publications
12
173
2
Order By: Relevance
“…Lately, the ability of adjuvants to alter the nature of immune responses has received considerable attention. For example, the influence of adjuvants on the pattern of cytokines produced by T helper (Th) cells is of great interest because of the importance of different Th cell subsets for generation of protective immunity against certain infectious diseases [83][84][85]. Several studies in murine models have addressed this issue with regard to ISCOMs.…”
Section: Modulation Of T Cell Responses By Iscomsmentioning
confidence: 99%
“…Lately, the ability of adjuvants to alter the nature of immune responses has received considerable attention. For example, the influence of adjuvants on the pattern of cytokines produced by T helper (Th) cells is of great interest because of the importance of different Th cell subsets for generation of protective immunity against certain infectious diseases [83][84][85]. Several studies in murine models have addressed this issue with regard to ISCOMs.…”
Section: Modulation Of T Cell Responses By Iscomsmentioning
confidence: 99%
“…It is possible that regimens using different cytokines, such as IL-12 [20], higher concentrations of cytokines, different combinations of cytokines, or longer incubations could result in even higher levels of cytotoxicity in this group of patients. It should be emphasized, however, that there is no current empirical evidence that augmenting NK or ADCC functions in patients with advanced HIV infection will result in clinical benefits.…”
Section: Discussionmentioning
confidence: 99%
“…For each subject, unactivated and lymphokine-activated specimens were assayed in parallel. Twenty per cent lytic units (LU 20 ) were calculated from the four E:T ratios utilizing software generously provided by Dr Hugh Pross [12].…”
Section: Measurement Of Cytotoxicitymentioning
confidence: 99%
“…Restoration of cell-mediated immune responses in vitro was not restricted to anti-CD28 MoAb, as it has recently been shown that IL-12 was also able to restore antigen-specific proliferation of CD4 T cells from HIV-infected individuals [19]. IL-12 also appears to inhibit AICD (G. Shearer, personal communication).…”
Section: Discussionmentioning
confidence: 99%